Polarization features of acoustic spectra in uniaxial and biaxial nematic liquid crystals - Kovalevsky, M.Y.; Logvinova, L.V.; Matskevych, V.T. (Вопросы атомной науки и техники, 2012)
The results of investigation of uniaxial and biaxial nematic liquid crystals dynamics with molecules of the various forms are presented. These condensed matters possess internal spatial anisotropy and for their adequate description introduction of additional dynamic quantities is necessary. They are vectors of spatial anisotropy and conformational degrees of freedom. Investigation of dynamics of the given condensed matters is based on Hamiltonian formalism in which framework the nonlinear dynamic equations for uniaxial and biaxial nematic liquid crystals are derived. Spectra of collective excitations are obtained and their polarization features are investigated. Представлены результаты исследования динамики одноосных и двухосных нематических жидких кристаллов с молекулами различной формы. Эти конденсированные среды обладают внутренней пространственной анизотропией, и для их адекватного описания необходимо введение дополнительных динамических переменных. Ими являются векторы пространственной анизотропии и конформационные степени свободы. Исследование динамики данных конденсированных сред базируется на гамильтоновом формализме, в рамках которого выведены нелинейные уравнения динамики для одноосных и двухосных нематических жидких кристаллов. Получены спектры коллективных возбуждений и исследованы их поляризационные особенности. Представлено результати досліджень динаміки одновісних та двовісних нематичних рідких кристалів з молекулами різної форми. Ці конденсовані середовища мають внутрішню просторову анізотропію, тож для їх адекватного опису необхідно введення додаткових динамічних змінних. Ними є вектори просторової анізотропії та конформаційні ступені свободи. Дослідження динаміки даних конденсованих середовищ базується на гамільтоновому формалізмі, у рамках якого виведені нелінійні рівняння динаміки для одновісних та двовісних нематичних рідких кристалів. Отримано спектри колективних збуджень та досліджено їх поляризаційні особливості.